BOWEL ULTRASOUND ELASTOGRAPHY IN ULCERATIVE COLITIS: A COMPREHENSIVE REVIEW - Yahya Almansoury, Muhammad Abdel-Gawad, Mohammed Tag-Adeen, Ghada M. Abdelrazek, Wageeh A. Ali, Zainelabdeen Ahmed, (Chelonian Research Foundation, 2024)
Ulcerative colitis (UC) is a chronic inflammatory bowel disease affecting the large intestine. Accurate assessment of disease activity is crucial for optimal management and treatment decisions. Bowel ultrasound elastography (BUE) is an emerging non-invasive technique that measures tissue stiffness and can provide valuable insights into the inflammatory status of the bowel wall in patients with UC. This review aims to provide a comprehensive overview of the current literature on bowel ultrasound elastography in UC, discussing its principles, advantages, limitations, and potential clinical applications.